Novel Insights on the Regulation of B Cell Functionality by Members of the Tumor Necrosis Factor Superfamily in Jawed Fish - Tafalla, Carolina; Granja, Aitor G. (Frontiers in Immunology, 2018)
Most ligands and receptors from the tumor necrosis factor (TNF) superfamily play very important roles in the immune system. In particular, many of these molecules are essential in the regulation of B cell biology and B cell-mediated immune responses. Hence, in mammals, it is known that many TNF family members play a key role on B cell development, maturation, homeostasis, activation, and differentiation, also influencing the ability of B cells to present antigens or act as regulators of immune responses. Evolutionarily, jawed fish (including cartilaginous and bony fish) constitute the first animal group in which an adaptive immune response based on B cells and immunoglobulins is present. However, until recently, not much was known about the expression of TNF ligands and receptors in these species. The sequences of many members of the TNF superfamily have been recently identified in different species of jawed fish, thus allowing posterior analysis on the role that these ligands and receptors have on B cell functionality. In this review, we summarize the current knowledge on the impact that the TNF family members have in different aspects of B cell functionality in fish, also providing an in depth comparison with functional aspects of TNF members in mammals, that will permit a further understanding of how B cell functionality is regulated in these distant animal groups.